Using Of Recycled Rubber Tires And Steel Lathes Waste As Fibbers To Reinforcing Concrete - Jasim Mohammed, Hasan; Hadi Abbas, Abbas; Abbas Husain, Muhammed (Iraqi Journal of Civil Engineering, 2013)
This research paper is accomplished to study the effect of using waste fibers in properties of concrete . Steel lathe waste fibers are added by percentages of (4, 6 and 8 %) from weight of concrete and a percentages of concrete coarse aggregate are replaced by rubber tires waste fibers in a ratios of (5, 10 and 15%) by volume . Besides to that, the combined fibers are used steel lathe waste fibers by adding (4, 6 and 8 %) with constant replacing of rubber tires waste fibers of (10 %). The results showed that adding of steel lathe waste fibers in plain concrete enhances its strength under compression about (15%) and tension about (20%), while rubber tires waste reduced both of compression about (80 %) and tension about (51%) strengths .Also the compression and tension strengths are reduced (88% and 30%) respectively with using combined fibers . The dry concrete density of lathe waste fibers concrete is (2345-2365kN/m3) , the rubberized concrete density is (2130-2240kN/m3) and for combined fibers concrete density (2025-2180 kN/m3).